Global Health Initiatives to Reduce Malaria Morbidity in School-aged Children - Andrew J. Macnab (GHMJ (Global Health Management Journal), 2020)
Background: To review global initiatives to reduce the burden of disease from malaria on school-aged children. The focus is on approaches with potential to reduce mortality and morbidity, improve the health and ability of children to attend school, avoid malaria impacting their potential academic achievement, and minimize the risk of short- and long-term cognitive impairment. Methods: Literature searches using defined terms related to malaria and education, and a scoping review of the key literature selected, to provide a narrative summary of the challenges and potential solutions identified. Results: There is robust evidence that school-aged children are particularly vulnerable to malaria, and need special measures to protect them; calls are widespread for better diagnostic approaches and program innovation because of current levels of malaria-related morbidity and mortality. School-based programs that educate children broadly on causation, prevention and care required can improve access to timely diagnosis and treatment; however, currently national malaria control interventions do not specifically target school-age children. The literature describes intervention strategies that include seasonal chemoprophylaxis, intermittent protective treatment and antimalarial therapy linked to mass drug administration for neglected tropical diseases. Recently, a community participatory intervention model based on WHO-endorsed diagnostic and treatment principles has taught teachers to screen all children sick at school using rapid point-of-care diagnostic testing and treat promptly with Artemesinin combination therapy; morbidity and absenteeism are significantly reduced. There is no consensus on the optimal intervention strategy; approaches will need to vary, but evidence of ‘what works and why' exists to guide constructive implementation measures in each endemic region. Conclusion: Malaria exemplifies how health inequity negatively impacts a child's health and ability to benefit from education, yet simple and effective school-based approaches exist that positively impact morbidity, provide access to WHO-endorsed diagnosis and treatment, are applicable worldwide and can increase the capacity of children to learn. Keywords: Absenteeism; Artemesinin Combination Therapy; Cognitive Impairment; Intermitient Protective Treatment; Rapid Diagnostic Testing; Seasonal Malaria Chemoprophylaxis; Teachers Received: 14 May 2020 Reviewed: 14 June 2020 Revised: 28 June 2020 Accepted: 28 June 2020 DOI: 10.35898/ghmj-41578